Enlightenment now [compact disc, unabridged] : the case for reason, science, humanism, and progress - Pinker, Steven, 1954- (Penguin Audio, 2018)
An assessment of the human condition in the twenty-first century presents data demonstrating that life quality, health, prosperity, safety, peace, knowledge, and happiness are on the rise throughout the world because of the Enlightenment ideal of using reason and science.